2022
DOI: 10.3389/ftox.2022.836447
|View full text |Cite
|
Sign up to set email alerts
|

Particle Safety Assessment in Additive Manufacturing: From Exposure Risks to Advanced Toxicology Testing

Abstract: Additive manufacturing (AM) or industrial three-dimensional (3D) printing drives a new spectrum of design and production possibilities; pushing the boundaries both in the application by production of sophisticated products as well as the development of next-generation materials. AM technologies apply a diversity of feedstocks, including plastic, metallic, and ceramic particle powders with distinct size, shape, and surface chemistry. In addition, powders are often reused, which may change the particles’ physico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 179 publications
1
17
0
Order By: Relevance
“…An exception is crystalline silica particles, where studies have demonstrated both phagocytosis-dependent ( 41 ) and -independent ( 78 ) NLRP3 inflammasome activation. These contrasting results may be due to differences in the properties of the silica particles, including size, shape, surface properties, or formation of a protein corona coating the particles ( 79 ). Following the formation of the phagolysosome, particles may interact with the (phago)lysosomal membrane leading to lysosomal membrane permeabilization (LMP) or rupture with subsequent release of lysosomal content into the cytosol that in turn will activate the NLRP3 inflammasome.…”
Section: Nlrp3 Inflammasome Activation By Particulatesmentioning
confidence: 99%
“…An exception is crystalline silica particles, where studies have demonstrated both phagocytosis-dependent ( 41 ) and -independent ( 78 ) NLRP3 inflammasome activation. These contrasting results may be due to differences in the properties of the silica particles, including size, shape, surface properties, or formation of a protein corona coating the particles ( 79 ). Following the formation of the phagolysosome, particles may interact with the (phago)lysosomal membrane leading to lysosomal membrane permeabilization (LMP) or rupture with subsequent release of lysosomal content into the cytosol that in turn will activate the NLRP3 inflammasome.…”
Section: Nlrp3 Inflammasome Activation By Particulatesmentioning
confidence: 99%
“…This inflammasome may be used as a sensor for detecting the immunotoxicity of MNPs. 231 Polystyrene MNPs triggered ROS buildup and activation of the NLRP3 inflammasome in human primary macrophages, 232 human monocytic (THP-1) 233 and mouse lung (MLE-12) cell lines, 234 and in mouse hepatocytes (AML12 cell line). 36 Polystyrene MNPs have been proven to activate the NLRP3/caspase-1 signaling pathway in rat 235 and mouse 236 models in vivo , triggering inflammatory reactions and pyroptosis.…”
Section: Interaction With the Circulatory Systemmentioning
confidence: 99%
“…(5) MNPs have been discovered to be phagocytosed by immune cells, such as macrophages, as evidenced by an increase in the generation of proinflammatory cytokines (interferons, interleukins, tumor necrosis factors, NLRP3 inflammasome, 231 etc. ) and prostaglandins.…”
Section: Key Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…The nanoparticle emission of laser-DED machines has been recognized, and some studies have already addressed the chemical and physical characterization of the emitted particles [ 10 ] and investigated occupational health-related issues [ 5 , 11 ]. The toxic properties of metal nanoparticles are now well known [ 5 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ] and their effects need to be taken into account in working environment design and laser-DED machine construction. Although exposure protection and regulatory measures in related industries (welding, etc.)…”
Section: Introductionmentioning
confidence: 99%